Assessing Africa’s food and nutrition security situation - Benson, Todd (International Food Policy Research Institute, 2004)
...in more than a dozen African countries the rate of undernourishment is more than 40 percent, exceeding 50 percent in those countries experiencing or emerging from armed conflict. As a result, more than a third of African children suffer stunted growth and face a range of physical and cognitive challenges not faced by their better fed peers. Ultimately, undernutrition underlies around 2.9 million deaths in Africa annually — more than a quarter of all the deaths occurring on the continent each year. The economic costs of such widespread undernutrition are enormous. This is because the economic growth of each nation — which requires enhanced economic productivity — depends upon broad improvements being made in the intellectual and technical capacity of its population. But, this in turn depends upon people receiving adequate nutrition, particularly women in their childbearing years and young children. So, only once African countries have secured the basic food and nutritional needs of their populations will they be able to achieve the broad-based economic growth necessary to reduce." -- from Text